2020
DOI: 10.1016/j.ygyno.2019.11.123
|View full text |Cite
|
Sign up to set email alerts
|

Blood steroid levels predict survival in endometrial cancer and reflect tumor estrogen signaling

Abstract: A clinically available panel of steroid hormones was analyzed in 100 endometrial cancer patient plasma samples. • Low 17OH-progesterone, 11-deoxycortisol and androstenedione associated to aggressive tumor characteristics. • 17OH-progesterone and 11-deoxycortisol predicted poor survival independent of preoperative risk classification. • Genes associated with estrogen signaling were enriched in tumors of patients with high steroid levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“… 30 Another research demonstrated that total TAT, VAT, and SAT were all related to plasma levels of estrone and estradiol, but not with VAT ratios. 31 Among the 115 cases of EC in this study, the differences in clinicopathologic features between the patients with high SAT lied in increased PR expression. This is consistent with another research by Mauland et al 32 : by analyzing the distribution of abdominal adipose tissue in 170 patients with EC, these researchers found that an increase in abdominal SAT volume was related to positive PR expression.…”
Section: Discussionmentioning
confidence: 79%
“… 30 Another research demonstrated that total TAT, VAT, and SAT were all related to plasma levels of estrone and estradiol, but not with VAT ratios. 31 Among the 115 cases of EC in this study, the differences in clinicopathologic features between the patients with high SAT lied in increased PR expression. This is consistent with another research by Mauland et al 32 : by analyzing the distribution of abdominal adipose tissue in 170 patients with EC, these researchers found that an increase in abdominal SAT volume was related to positive PR expression.…”
Section: Discussionmentioning
confidence: 79%
“…biopsy in combination with the preoperative ultrasound image available. However, these preoperative data are often inconsistent with the postoperative data 26 , indicating the need for the emergence of alternatives that increase the accuracy of the prognosis and diagnosis of this disease without adversely affecting the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, steroids might serve as good predictors in diseases such as endometriosis or ovarian cancer: LC-MS applied to ectopic lesions revealed a specific pattern for P4 and testosterone (T) compared to serum [14]. In endometrial cancer, blood steroid levels predict survival in endometrial cancer and reflect tumor estrogen signaling [15]. In ovarian cancer, steroid hormone synthesis by the ovarian stroma surrounding epithelial ovarian tumors may participate in ovarian tumorigenesis [16].…”
Section: Introductionmentioning
confidence: 99%
“…In ovarian cancer, steroid hormone synthesis by the ovarian stroma surrounding epithelial ovarian tumors may participate in ovarian tumorigenesis [16]. Circulating 17α-hydroxyprogesterone (17OHP4) and 11-deoxycortisol (S) have been suggested as prognostic markers for endometrial cancer survival [15]. Finally, T was positively associated with epithelial ovarian cancer risk [17].…”
Section: Introductionmentioning
confidence: 99%